The impact of grassland ecological compensation policy on overgrazing behavior of herdsmen with non-pastoral employment: evidence from Inner Mongolia, China - Ouyang, Wenjie; Ju, Fang; Han, Jiali; Gai, Zhiyi; Zhang, Bao (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe Grassland Ecological Compensation Policy (GECP) not only improves the grassland ecosystem, but also encourages more and more full-time herdsmen to take up non-pastoral employment. This raises an important question: does non-pastoral employment have a differential impact on overgrazing among herdsmen, and how does it affect the effectiveness of policy implementation? Addressing this question will provide a scientific foundation for the sustainable development of grassland pastoral areas.MethodsUtilizing data from 542 herdsmen in the pastoral areas of Inner Mongolia, this paper employs a double difference model to analyze the impact of the GECP on the overgrazing behavior of herdsmen with non-pastoral employment.ResultsThe research findings indicate that: (1) The GECP exacerbates overgrazing behavior among full-time pastoral herdsmen (PH1 herdsmen) and those with non-pastoral employment at low levels (PH2 herdsmen), while it mitigates such behavior among herdsmen with non-pastoral employment at high levels (PH3 herdsmen); (2) Non-pastoral employment significantly enhances the inhibitory effects of the GECP on herdsmen’s overgrazing behavior; (3) The influence of grassland rent-in and barn feeding on herdsmen’s overgrazing behavior varies according to the levels of non-pastoral employment among herdsmen.DiscussionTherefore, this paper suggests that the government should continue to optimize the policy, along with differentiated subsidy methods and content. It also advocates for guiding herdsmen towards non-pastoral employment to achieve sustainable development of both ecological and economic aspects in pastoral areas.